Void nucleation, growth and closure in cold forging: An uncoupled modelling approach - R. Gitschel; A. Schulze; A.E. Tekkaya (Advances in Industrial and Manufacturing Engineering, 2023)
Forward rod extrusion experiments with high extrusions strains show a decrease of void area during forming. Most of the established damage modelling approaches have been developed without that knowledge and do not adequately cover the effect of void closure. Furthermore, many so called coupled models focus on the effect of ductile damage on the plastic flow of the material which results in more complex and numerically expensive models. But the effect of voids on plastic flow is insignificant for many cold forging applications, as shown in recent experiments. Thus, an uncoupled model is proposed that covers the effects of void nucleation, growth and closure. The proposed model is calibrated using void area fractions measured in forward rod extrusion experiments. A validation for various load paths shows good accordance with experimental data for void closure conditions under low triaxiality as well as for void evolution under higher triaxialities.